2021
DOI: 10.3389/fphar.2021.705636
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Urinary Biomarkers as Diagnostic and Prognostic Predictors of Acute Kidney Injury Associated With Vancomycin

Abstract: Introduction: The incidence of acute kidney injury (AKI) related to vancomycin is variable, and several risk factors related to the treatment and patients may explain the nephrotoxicity. The role of urinary biomarkers in AKI related to vancomycin is unknown.Objective: The aim of this study was to evaluate the role of urinary IL-18, KIM-1, NGAL, TIMP-2, and IGFBP7 as diagnostic and prognostic predictors of AKI related to vancomycin.Methods: A prospective cohort study of patients receiving vancomycin and admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…[38] However, despite its potential role as a predictor of vancomycin-induced AKI, studies comparing urinary biomarkers, including KIM-1, as early detection markers for drug-induced AKI have yielded inconsistent results. [37,39,40] Therefore, further studies with a larger population are warranted to elucidate the role of KIM-1.…”
Section: Discussionmentioning
confidence: 99%
“…[38] However, despite its potential role as a predictor of vancomycin-induced AKI, studies comparing urinary biomarkers, including KIM-1, as early detection markers for drug-induced AKI have yielded inconsistent results. [37,39,40] Therefore, further studies with a larger population are warranted to elucidate the role of KIM-1.…”
Section: Discussionmentioning
confidence: 99%
“…The [TIMP-2] × [IGFBP-7] value obtained on day 1 of vancomycin administration was independently associated with VA-AKI (p < 0.001) [65]. A prospective cohort study of 94 patients receiving vancomycin found that the urinary NGAL level between 96 and 144 hrs (OR 1.123, 95%CI 1.096-1.290, p = 0.03) was a predictor of AKI development, whereas a higher urinary x[IGFBP-7]/Cr between 144 and 192 hrs (OR 1.26, 95%CI 1.092-1.543, p = 0.03) was a predictor of non-recovery of VA-AKI [64]. In addition, a recent study by Awdishu et al [12] found that urinary concentrations of some inflammatory proteins (namely, complement C3, C4, galectin-3-binding protein, fibrinogen, alpha-2 macroglobulin, immunoglobulin heavy constant mu, and serotransferrin) increased after nephrotoxic injury in patients with VA-AKI.…”
Section: Biomarkers For Detecting Va-akimentioning
confidence: 99%
“…Interestingly, cyclosporine dose reduction in these patients led to decreased urine β2-microglobulin [60]. In addition, based on results of a cohort investigation, urinary NGAL levels between 96 and 144 h and urinary [TIMP-2]•[IGFBP7] normalized by urinary creatinine between 144 and 192 h of vancomycin use were predictors of developing AKI during hospital stay and recovery of AKI at the time of hospital discharge, respectively [61]. There is the possibility of tracking patients' improvement with DIKD using novel biomarkers.…”
Section: Movement Between Categoriesmentioning
confidence: 99%